Pengaruh Media Sosial terhadap Perilaku Konsumtif Mahasiswa di Pontianak - Muhammad Faisal (Journal on Education, 2024)
This study aims to identify the impact of social media usage on the consumptive behavior of students in Pontianak, analyze the dominant factors influencing consumptive behavior through social media, and provide strategic recommendations to mitigate the negative effects of social media. Employing a quantitative approach with a descriptive survey method, the research examines the relationship between social media usage frequency and the level of consumptive behavior. The population consists of active students from four universities in Pontianak: Universitas Tanjungpura (UNTAN), Institut Agama Islam Negeri (IAIN) Pontianak, Politeknik Negeri Pontianak (POLNEP), and Universitas Muhammadiyah Pontianak (UMP). A sample of 300 students was selected using simple random sampling to represent the population. Data was collected through an online questionnaire distributed via Google Forms, covering demographic information, social media usage frequency, and consumptive behavior. Data analysis techniques using SPSS version 25 included descriptive analysis, normality tests, linear regression analysis, and correlation tests. The results show that 87% of students use social media for more than 3 hours daily, with Instagram, TikTok, and Facebook being the most frequently used platforms. A significant positive relationship was found between social media usage frequency and consumptive behavior (β = 0.72, p < 0.01), and exposure to advertisements and influencers has a strong correlation with consumptive behavior (r = 0.68, p < 0.05). These findings underscore the need for digital literacy to help students make more informed consumption decisions and mitigate the negative impacts of social media.